HEY MOM : STORIES FOR MY MOTHER, BUT YOU CAN READ THEM TOO - Anderson, Louie (New York : TOUCHSTONE, 2018)
Louie Anderson, New York Times bestselling author and Emmy Award-winning comedian currently starring in Zach Galifianakis's Baskets , shares his journey of turning life's challenges into joy, as well as plenty of wisdom he's still discovering from his late mother.
April 2015 -- It's about time -- Gone but never forgotten -- Tenth child -- Premiere -- Birthday girl -- Training day -- Silent dancing -- You and me -- Daily prayer -- The hair twirlers -- Finding Ora -- One thing I really miss -- Each parent got a book -- Life sucks without bread -- Louie Anderson is dead -- No family feud -- That's somebody's baby -- If there are cheeseheads in Bucharest, blame me -- Who, me? -- I am Christine -- My first lady -- Thank you, brother -- Truth ranger -- New Year's Eve! (minus the booze) -- 2016 -- Yes, man -- Podcasts and home -- That was your baby, Mom -- A moment I think I wish I hadn't missed followed by one I'm so happy I didn't -- Life is funny -- Comedian? Movie star? Leader of the free world? -- Make your date -- Sweet Lisa -- Big shot -- Stranger things -- Stand-up people -- Nominee -- You gave away a child, or two -- Midwesterners -- 70% disabled, pending 100% -- Penguin costume time -- I don't have to smile like I'm happy for someone else! -- Note to Thomas Wolfe: You never actually leave home -- My TV family -- Big & beautiful -- Older -- Full moon -- Life is a performance, old chum -- Seduce, exploit, abandon -- 2017 -- Jesus calling -- What are we waiting for? -- I miss them all -- Fat camp -- Myworld -- Family peace -- Hat day -- Doing what we shouldn't, not doing what we should -- Big underwear -- When it rains it pours -- 12-step -- Fellowship -- It's your faults, Mom -- Writers need deadlines -- This book is not about you, Dad, except when it is -- Reunion -- Season 3 -- The sorrow sparrow -- Defending champ -- The day you died -- To everyone who is a Mom or had a mom.
Keywords: Anderson, Louie. -- New York Times bestselling author and Emmy Award-winning comedian; Mothers -- United States -- Humor; Mother and child -- United States -- Humor; Comedians -- Family relationships -- United States; Comedians -- United States -- Biography; Mother and child -- United States